'Everything just seems much more right in nature': How veterans with post-traumatic stress disorder experience nature-based activities in a forest therapy garden. Issue 1 (30th March 2016) - Poulsen, Dorthe Varning; Stigsdotter, Ulrika K; Djernis, Dorthe; Sidenius, Ulrik
Available evidence shows that an increasing number of soldiers are seeking help for post-traumatic stress disorder. The post-traumatic stress disorder condition has big emotional and psychological consequences for the individual, his/her family and the society. Little research has been done to explore the impact of nature-based therapy for veterans with post-traumatic stress disorder although there is a growing amount of evidence pointing towards positive outcome. This qualitative study aims to achieve a deeper understanding of this relationship from the veteran's perspective. Eight Danish veterans participated in a 10-week nature-based therapy. Qualitative interviews were conducted and analysed using the interpretative phenomenological method. The results indicated that the veterans have achieved tools to use in stressful situations and experienced an improvement in their post-traumatic stress disorder symptoms.